Comparison of a few Sward Forming Grasses for their Effectiveness in Stabilisation of Water-Ways - Sachdeve, C. P.; Gill, B. S.; Dutta, Y.; Daniel, M. M. (Indian Forester, 1976)
One of the main problems of soil conservation in high rainfall areas is to get rid of the excess rain water in the form of surface runoff without damaging land. There are vegetative and mechanical practices for such control. The grass roots are known for physical help in entrapping the soil particles which otherwise tend to move away with the runoff. With a view to selecting a grass most suitable to clothewater-way in this hilly tract and thereby reduce the soil loss, an experiment was laid out at Soil Conservation Research Centre Chatra, Nepal. The Soil Conservation Research Station Chatra (Nepal) (87°E aad 27°N) on Chatra loamy sand analysing, course sand 15.68%, fine sand 47.92%, silt 19.38% aad clay 12.38% has a characteristics of Terai climate with a mansoonic annual precipitation ranging from 1,750 to 2500 mean daily maximum temperature 20°0 to 30°C and humidity rarely below 90% except in mid summer. Elevation is 110 metres above mean sea level. As a result of the experiment, it was found that the Thin napier grass i.e. Pennisetum polystachyon gave significantly higher yield, retained more silt deposition and had larger basal area coverage.